Voluntary Partnership Agreement between the United Kingdom of Great Britain and Northern Ireland and the Republic of Indonesia on Forest Law Enforcement, Governance and Trade in Timber Products into the United Kingdom of Great Britain and Northern Ireland, Jakarta, 29 March 2019. ([2019-04-08]) - Unknown
No abstract available